Dr. Palley and the merits of conflict - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2024)
Controversy is vital in the pursuit of knowledge. Constructive dispute can drive intellectual growth and deepen understanding within a field. However, mutual respect, thorough engagement, and intellectual humility are necessary for productive exchanges. In this vein, I clarify in my response to Tom Palley's critique of my article that I did not argue against his claim regarding social conflict in Keynesian economics. However, I questioned whether social conflict is the sole ontological fault line, as Palley suggests. Additionally, I highlighted the distinction between Keynes' economics and Keynesian economics, challenging Palley's lumping them together as part of a liberal project. In conclusion, Palley's assertions regarding the absence of social conflict in Keynesian economics and its implications for economic laws lack foundation.
Keywords: A14; B40; B51; E11; E12; 330; Keynes; social conflict; paradigm shift